Seasonality of monoterpene emission potentials in Quercus ilex and Pinus pinea: Implications for regional VOC emissions modeling - KEENAN, Trevor; Niinemets, Ülo; Sabaté, Santi; Gracia, Carlos; Penuelas, Josep (Journal of Geophysical Research: Atmospheres, 2009)
VOC emissions from terrestrial ecosystems provide one of the principal controls over oxidative photochemistry in the lower atmosphere and the resulting air pollution. Such atmospheric processes have strong seasonal cycles. Although similar seasonal cycles in VOC emissions from terrestrial ecosystems have been reported, regional emissions inventories generally omit the effect of seasonality on emissions. We compiled measurement data on seasonal variations in monoterpene emissions potentials for two evergreen species (Quercus ilex and Pinus pinea) and used these data to construct two contrasting seasonal response functions for the inclusion in monoterpene emission models. We included these responses in the Niinemets et al. model and compared simulation results to those of the MEGAN model, both with and without its predicted seasonality. The effect of seasonality on regional monoterpene emissions inventories for European Mediterranean forests dominated by these species was tested for both models, using the GOTILWA+ biosphere model platform. The consideration of seasonality in the Niinemets et al. model reduced total estimated annual monoterpene emissions by up to 65% in some regions, with largest reductions at lower latitudes. The MEGAN model demonstrated a much weaker seasonal response than that in the Niinemets et al. model, and did not capture the between species seasonality differences found in this study. Results suggest that previous regional model inventories based on one fixed emission factor likely overestimate regional emissions, and species-specific expressions of seasonality may be necessary. The consideration of seasonality both largely reduces monoterpene emissions estimates, and changes their expected seasonal distribution.
Keywords: Holm oak; Italian stone pine; Models; regional inventory; Seasonality; VOC emissions

The terpenoid emission pattern of Quercus coccifera L coincides with the emission pattern found with Quercus ilex L - Hansen, U.; Seufert, G. (PROCEEDINGS OF EUROTRAC SYMPOSIUM `96 - TRANSPORT AND TRANSFORMATION OF POLLUTANTS IN THE TROPOSPHERE, VOL 2: EMISSIONS, DEPOSITION, LABORATORY WORK AND INSTRUMENTATION, 1997)
Monoterpene and isoprene emission rates from Kermes or Holly oak (Quercus coccifera L.), an evergreen shrub or small tree which is widely present in the Mediterranean area, were investigated in a greenhouse using a dynamic enclosure technique, Monoterpenes emitted with the highest rates from Quercus coccifera were alpha-pinene, sabinene and beta-pinene. alpha-pinene contributed 41 % to the total monoterpene emission, sabinene 28 % and beta-pinene 25 %. The isoprene emission rate was 0.7 % of the total monoterpene emission rate. Standardisation to 30 degrees C revealed a total monoterpene emission rate of 18.7 mu g gLDW(-1) h(-1). The data show that terpenoid emissions from Kermes oak (Quercus coccifera L.) are qualitatively and quantitatively similar to those of Helm oak (Quercus ilex L.). Both species have to be considered as strong monoterpene emitters, Emissions are considerably higher compared to the emission factor of 1.2 mu g C gLDW(-1) h(-1) which was assumed to represent the monoterpene emission rate from Mediterranean ecosystems at standard conditions in a study about a global model of natural VOC emissions.
The following values have no corresponding Zotero field: periodical: PROCEEDINGS OF EUROTRAC SYMPOSIUM `96 - TRANSPORT AND TRANSFORMATION OF POLLUTANTS IN THE TROPOSPHERE, VOL 2: EMISSIONS, DEPOSITION, LABORATORY WORK AND INSTRUMENTATION pub-location: ASHURST LODGE, SOUTHAMPTON, HANTS, ENGLAND S04 2AA
Keywords: alpha-pinene; beta-pinene; isoterpene; Mediterranean area; Monoterpene; Quercus coccifera L.; sabinene; terpenoid; VOC emissions

The terpenoid emission pattern of Quercus coccifera L coincides with the emission pattern found with Quercus ilex L - Hansen, U; Seufert, G (PROCEEDINGS OF EUROTRAC SYMPOSIUM `96 - TRANSPORT AND TRANSFORMATION OF POLLUTANTS IN THE TROPOSPHERE, VOL 2: EMISSIONS, DEPOSITION, LABORATORY WORK AND INSTRUMENTATION, 1997)
Monoterpene and isoprene emission rates from Kermes or Holly oak (Quercus coccifera L.), an evergreen shrub or small tree which is widely present in the Mediterranean area, were investigated in a greenhouse using a dynamic enclosure technique, Monoterpenes emitted with the highest rates from Quercus coccifera were alpha-pinene, sabinene and beta-pinene. alpha-pinene contributed 41 % to the total monoterpene emission, sabinene 28 % and beta-pinene 25 %. The isoprene emission rate was 0.7 % of the total monoterpene emission rate. Standardisation to 30 degrees C revealed a total monoterpene emission rate of 18.7 mu g gLDW(-1) h(-1). The data show that terpenoid emissions from Kermes oak (Quercus coccifera L.) are qualitatively and quantitatively similar to those of Helm oak (Quercus ilex L.). Both species have to be considered as strong monoterpene emitters, Emissions are considerably higher compared to the emission factor of 1.2 mu g C gLDW(-1) h(-1) which was assumed to represent the monoterpene emission rate from Mediterranean ecosystems at standard conditions in a study about a global model of natural VOC emissions.
Keywords: alpha-pinene; beta-pinene; isoterpene; Mediterranean area; Monoterpene; Quercus coccifera L.; sabinene; terpenoid; VOC emissions